A qualitative approach in comparing six cities toward a resilient response plan: COVID-19 and inequalities - Rim Meziani; Paola Rizzi; Ayah Alkhatib; Maya Wacily; Heba Hejji; Zeina Hamam (City, Territory and Architecture, 2024)
The comparative analysis shows that poverty, culture, and governance are primary factors that control the success of states under emergency.
Keywords: Cataract; Cost-saving; Refractive error; Tele-health; Telemedicine; Teleophthalmology; Tribal region of Gujarat